Wyniki produkcyjne gospodarstw trzodowych w Wielkopolsce na tle kraju jako wyznacznik konkurencyjności regionu - Stępień, Sebastian (Production Results of Pig Farms in Wielkopolska against Poland Background as a Determinant of Region Competitiveness, 2006)
The aim of the paper is to compare the production results, especially costs of raising, of pig farms in Wielkopolska and Poland as a whole, and to estimate the level of competitiveness of producers in the region determined by the prices and quality of animals for slaughter. The analysis comprises the period of 1990-2003 and concerns farms which managed the book-keeping for IERiGŻ in Warsaw.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 350-356